Los españoles en el México independiente: 1821-1950. Un estado de la cuestión - Lida, Clara E. (El Colegio de México, A.C., 2006)
The last twenty-five years have witnessed a proliferation of Mexican monographic works on Spaniards who migrated  to Mexico during the nineteenth and twentieth centuries. This allows us to approach  them from different viewpoints: qualitative and quantitative, national and local. This bibliographical review offers the reader an assessment of the knowledge  produced on the subject up to this moment,  and points out issues which still constitute important gaps.